Betty Boop. II - Fleischer, Dave, 1894-1979; Questel, Mae, 1910-1998; Poe, Bonnie, 1912-1993; Hines, Marjorie, 1909-2011; Fleischer Studios Inc.; National Telefilm Associates; Cinetel Films ([Los Angeles, CA] : [publisher not identified], 2014)
Six episodes from the famous cartoon Betty Boop.
Betty Boop's rise to fame -- A song a day -- A hunting we will go -- Little nobody -- A language all my own -- Swat the fly.
Title from the provider's web page.
Originally produced in the United States as motion pictures between 1934 and 1936.
Produced by Fleischer Studios and distributed by National Telefilm Associates.
Movie distributed by Cinetel for Digitalia Film Library.
Voice: Margie Hines, Mae Questel, Bonnie Poe.
Animated by David Tendlar, Nick Tafuri, Alfred Eugster, Rudolph Ecceman, Myron Waldman, Hicks Lokey, Samuel Stimson.
Keywords: Boop, Betty (Fictitious character) -- Drama; Animated films; Comedy films; Internet videos; Streaming video